2016
DOI: 10.21566/tarbitderg.280377
|View full text |Cite
|
Sign up to set email alerts
|

Göller Bölgesi İllerinde Yetiştirilen Nohut Genotiplerinin Bazı Kalite ve Teknolojik Özellikleri Yönünden Değerlendirilmesi

Abstract: ÖzAraştırma; Göller Bölgesinde yer alan illerden toplanan yerel nohut populasyonları ile yörede yetiştirilen tescilli nohut çeşitlerinin tane ve bazı teknolojik özelliklerinin belirlenmesi amacıyla 2013-2014 yıllarında SDÜ Ziraat Fakültesi Tarla Bitkileri laboratuarlarında yürütülmüştür. Isparta, Burdur, Denizli, Uşak ve Afyonkarahisar illerinde nohut tarımının yoğun yapıldığı ilçe ve köylerde, üretici tarlalarından farklı nohut genotipleri ile en fazla yetiştirilen tescilli çeşitlerin tohumları toplanmış, eba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
(2 reference statements)
1
5
0
3
Order By: Relevance
“…The local genotype of Bozkurt Çambaşı (1.20 a ) and the variety of Sezenbey (1.23 a ) provided the best average in terms of water absorption index (%) while the varieties of Hisar (0.95 i ) and Azkan (0.98 i ) gave the lowest average. Kaya et al (2016) have stated in their study that the water absorption interval of the genotypes is 0.47-3.46%. Uzun et al ( 2012) have stated in their study "Evaluation of Certain Selected Chickpea (Cicer arietinum L.) Lines in terms of Agronomic and Quality Characteristics" that there are significant differences (P<0.05) between the water absorption index (%) of the genotypes.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The local genotype of Bozkurt Çambaşı (1.20 a ) and the variety of Sezenbey (1.23 a ) provided the best average in terms of water absorption index (%) while the varieties of Hisar (0.95 i ) and Azkan (0.98 i ) gave the lowest average. Kaya et al (2016) have stated in their study that the water absorption interval of the genotypes is 0.47-3.46%. Uzun et al ( 2012) have stated in their study "Evaluation of Certain Selected Chickpea (Cicer arietinum L.) Lines in terms of Agronomic and Quality Characteristics" that there are significant differences (P<0.05) between the water absorption index (%) of the genotypes.…”
Section: Resultsmentioning
confidence: 97%
“…Yalcın et al (2018) have determined the seed coat rates (%) of genotypes as 5.21-6.0 in their study which was conducted in eight chickpea genotypes under the conditions of Afyonkarahisar and Yozgat provinces. Another study, which was conducted by Kaya et al (2016), and titled "Evaluation of Chickpea Genotypes Grown in the provinces of Lakes Region in terms of Certain Quality and Technological Properties", has revealed that seed coat rate is 0.66-3.07%. In another study conducted for 2 years, Damla-89 type of chickpea was used and seed coat rate has been determined as 5.46% (Mut and Gülümser, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu yüzden kalıntısız ürünler elde etmek, tarımda sürdürülebilirliği sağlıklı bir şekilde yürütmek için ülkemizdeki organik tarım ekim alanlarını arttırmamız gerekmektedir. Teknolojik özellikler arasında kalite parametresi olarak değerlendirilen elek analizi yetiştirme yerinin özelliklerine, çeşide ve yetiştirme koşullarına göre önemli farklılıklar gösterir (Kaya et al 2016). Bu çalışmada da 1991-2013 yılları arasında tescil edilen nohut çeşitlerinin kimyevi ve organik girdi kullanmadan doğal koşullarda yetiştirilmesi ile elde edilen tanelerin elek analiz değerleri, yıllara göre değişimi ve birbirleri ile ilişkileri araştırılmıştır.…”
Section: Introductionunclassified